2021
DOI: 10.3390/agriculture11100916
|View full text |Cite
|
Sign up to set email alerts
|

Phone App to Perform Quality Control of Pesticide Spray Applications in Field Crops

Abstract: It has been recognized for decades that low and inconsistent spray coverages of pesticide applications represent a major challenge to successful and sustainable crop protection. Deployment of water-sensitive spray cards combined with image analysis can provide valuable and quantitative insight into spray coverage. Herein we provide description of a novel and freely available smartphone app, “Smart Spray”, for both iOS and Android smart devices (iOS and Google app stores). More specifically, we provide a theore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…We observed markedly lower nymph emergence from no-choice compared to twochoice bioassays. This important result is not surprising, but it underscores the importance of insecticide spray coverage [38]. That is, low and inconsistent spray coverages with contact insecticides present insect pest females with a "choice" between treated and untreated (high-and low-risk) oviposition sites.…”
Section: Oviposition and Nymph Emergence In Response To Hosts And Riskmentioning
confidence: 90%
“…We observed markedly lower nymph emergence from no-choice compared to twochoice bioassays. This important result is not surprising, but it underscores the importance of insecticide spray coverage [38]. That is, low and inconsistent spray coverages with contact insecticides present insect pest females with a "choice" between treated and untreated (high-and low-risk) oviposition sites.…”
Section: Oviposition and Nymph Emergence In Response To Hosts And Riskmentioning
confidence: 90%
“…Based purely on genetics, a given insecticide may be expected to kill 100% of homozygous susceptible individuals. However, some survival of these insect pest individuals could be attributed to factors accounting for low and incomplete spray coverage of contact insecticides [31,32] and/or sublethal and non-uniform concentration of systemic insecticides in portions of crop canopies [33]. In this theoretical scenario, the total pest population reaches 80% of carrying capacity after about 11 generations, and this coincides with the resistance allele frequency reaching 50%.…”
Section: How To Use the Interactive Teaching Toolmentioning
confidence: 95%
“…Lewis e Hamby (2020) observed that optimizing coverage is a crucial component of sugarcane (Saccharum officinarum L.) pest management. Nansen et al (2021) reported that inconsistent and low coverage is particularly concerning when contact insecticides are applied. Greater coverage increases the likelihood of contact between the target and the product.…”
Section: Droplet Spectrummentioning
confidence: 99%